Harmonising Cosmopolitanism and Communitarianism: Goals of EU Labour Migration Policy - Popović, Nella; Petek, Ana (Journal of international migration and integration, 2025)
EU migration policy for labour migrants has a complex history and an unforeseeable future regardless of its high relevance, as it sways between the opposing political positions in favour of and against open borders. By combining normative political theory and policy design analysis, this paper aims at detecting points of reconciliation between cosmopolitan and communitarian approaches to labour migrants’ issues with the aim to contribute to EU migration policy development. A systematic empirical analysis rests on qualitative methodology and is guided by the rules of thematic analysis. Detailed coding of policy goals within diverse EU documents in the last 50 years revealed two models of EU migration policy goals targeting labour migrants: the political and security model and the economic and social model, both encompassing the admission and membership of labour migrants in the host communities. The main findings show that when it comes to third-country nationals, the issue of labour migrants’ entry is approached from a position coherent with communitarianism, while cosmopolitan views are more present at the level of their membership. The research has identified potential areas of reconciliation that should be explored in future policymaking: greater inclusion of labour migrants in decision-making processes; enhancing assistance to third countries; linking more closely the freedom of movement, antidiscrimination, and equality to admission rules; further strengthening of the freedom of religion, particularly for the employment of legally admitted long-term migrants; and building stronger accommodation of domestic cultures to migrants, not only vice versa.